The Influence of the Value Clarification Technique (VCT) Model Assisted by Interactive Video Media on the Learning Activities of Elementary School Civics Education Students : English - Hardiana; Muhajir; Andi Sugiati (Universitas Majalengka, 2024)
This study aims to analyze the influence of the Value Clarification Technique (VCT) model assisted by interactive video media on the learning activities of elementary school students in Pancasila and Civic Education (PPKn). This research employs a quantitative approach with a quasi-experimental design. The experimental group consists of 32 fifth-grade students in Lembaya, while the control group consists of 25 fifth-grade students in Cikoro, selected using purposive sampling and random sampling. Data were collected through observation, pretest and posttest questions, and documentation. Data analysis was conducted through prerequisite tests, including homogeneity and normality tests, followed by descriptive and inferential tests using t-test and Anova. The normality test was conducted using the Kolmogorov-Smirnov test to determine data distribution, with a significance criterion above 0.05, while the homogeneity test aimed to ensure the equality of variances between groups. The results of the analysis indicate a significant influence of the VCT model assisted by interactive video media on students' learning activities. The significant values obtained from the t-test and Anova indicate that students taught with the VCT model showed better improvement compared to those taught with conventional methods. These findings underscore the importance of integrating technology into education to enhance the quality of education and student engagement in PPKn learning. This research is expected to contribute to the development of more innovative and effective teaching methods in elementary schools.